White light generation controlled by changing the concentration of silver nanoparticles hosted by Ho3+/Tm3+/Yb3+ doped GeO2-PbO glasses - Camilo, Mauricio E. [UNESP] (2015)
Frequency upconversion (UC) experiments were performed with GeO2-PbO glasses, containing silver nanoparticles (NPs), doped with holmium (Ho3+), thulium (Tm3+) and ytterbium (Yb3+) ions. The samples were excited using a continuous-wave diode laser operating at 980 nm. The UC intensities and the colors of the samples were controlled by changing the concentrations of the rare-earth ions (REI) and the silver NPs nucleated inside the samples. The colors observed spanned the visible range from the red-yellow to the blue. For a particular combination of silver NPs and REI concentrations it was obtained white light generation corresponding to the CIE coordinates X = 0.33 and Y = 0.33.